Smart measure: precision measurement system with cloud integration - Mohd Radzi, Muhammad Farhan Hakimi; Mohd. Atan, Fadila; Mokhtar, Siti Musliha Ajmal; Sidik, Norbaiti (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Accurate measurement is vital in industries such as engineering, manufacturing, and healthcare, where precision ensures quality and efficiency. Traditional tape measures often fall short due to low accuracy, manual errors, limited unit conversion, and the inability to store measured values, leading to inconsistent workflows and inefficiencies. This project aims to develop an automatic calibration system using an ultrasonic sensor and an ESP32 microcontroller. By employing a time-to-distance conversion method, the system ensures precise measurements while eliminating the need for traditional measuring tools. Enhanced functionality includes unit conversion capabilities and integration with the Blynk cloud platform for storing and retrieving measured data, which improves workflow productivity and usability. The project scope involves the use of essential tools such as an ultrasonic sensor, DHT22 temperature sensor, LED, buzzer, LCD display, and the Blynk app, all programmed using the Arduino IDE. This innovative system addresses the limitations of conventional measurement methods, offering improved accuracy, expanded functionality, and greater efficiency for modern industrial applications. This solution represents a significant step toward advancing measurement technology, enhancing practicality, and meeting the growing demands for precision and adaptability in various fields.